ANALISIS PEMILIHAN JENIS PONDASI PADA PEMBANGUNAN JEMBATAN “LAE MARSABAN” PADA UPTD-SIDIKALANG WILAYAH KABUPATEN DAIRI (STUDI KASUS) - Ronald Rezeki Tarigan; Hottua Sitanggang (Universitas Quality, 2019)
Planning the foundation of a structure is a necessity by construction technicians. The strength of the upper structure is also influenced by the lower structure. Detailed research is needed for this foundation. The research location is on a bridge located in Sidikalang, Dairi Regency, North Sumatra, which is called the Lae Marsaban Bridge on the Sumbul Pegagan Section - Parikki - Pangiringan Link. 117 STA. 143 + 000 in Dairi District. Examination of soil type is carried out visually to determine the value of carrying capacity of the soil. According to the calculation and analysis of the planner, that this type of wells foundation has shown a construction that is able to support the bridge above it. Besides observing the condition and type of soil, calculating and planning the strength of management is a must. The foundation used is a sump foundation with a diameter of 2.5 meters and a depth of 8.4 meters, where the depth of hard soil is at 8.4 m. According to researchers, the implementation of the bridge is considered too excessive in terms of economic aspects. For this reason, more detailed and comprehensive research follow-up is needed.